2020
DOI: 10.1109/tcad.2019.2962779
|View full text |Cite
|
Sign up to set email alerts
|

Advance Interconnect Circuit Modeling Design Using Fractional-Order Elements

Abstract: Nowadays, the interconnect circuits' conduct plays a crucial role in determining the performance of the CMOS systems, especially those related to nano-scale technology. Modelling the effect of such an influential component has been widely studied from many perspectives. In this work, we proposed a new general formula for RLC interconnect circuit model in CMOS technology using fractional-order elements approach. The study is based on approximating an infinite transfer function of the CMOS circuit with a non-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…possessing fractional orders very near to 1 (see [45, Table 1] and [46, Table 3]), the straightforward current-voltage relation i(t) = Cdv(t)/dt has been simply used for describing their dynamical behavior. Some more advanced samples of benefiting from fractional-order dynamics in modeling of electrical components are modeling of onchip inductors constructed by the Siliconbenzocyclobutene technology [47], voltammetric sensors [48], on-chip interconnects in nanoscale CMOS circuits [49], CMOS metamaterial transmission lines [50] [51], and large three-dimensional RC networks [52].…”
Section: Circuits and Systems Modeled By Nonlinear Fractional-ordmentioning
confidence: 99%
“…possessing fractional orders very near to 1 (see [45, Table 1] and [46, Table 3]), the straightforward current-voltage relation i(t) = Cdv(t)/dt has been simply used for describing their dynamical behavior. Some more advanced samples of benefiting from fractional-order dynamics in modeling of electrical components are modeling of onchip inductors constructed by the Siliconbenzocyclobutene technology [47], voltammetric sensors [48], on-chip interconnects in nanoscale CMOS circuits [49], CMOS metamaterial transmission lines [50] [51], and large three-dimensional RC networks [52].…”
Section: Circuits and Systems Modeled By Nonlinear Fractional-ordmentioning
confidence: 99%
“…However, the pronounced nonlinearity inherent in DC-DC converters poses significant challenges in the construction of their precise mathematical models [7,8]. Studies have shown that fractional-order models are superior in characterizing the electrical properties of components in the context of DC-DC converters [9][10][11][12][13]. Applying fractional-order operators to mathematical modeling of DC-DC converters can provide a more comprehensive and accurate description of the electrical characteristics of DC-DC converters [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much research [17,18] has emerged on the practical realization of FOE and fractional-order systems, such as resistor and capacitor networks [19,20], singlecomponent realization [21], field-programmable gate arrays (FPGAs) [22] and generalized impedance converter [23]. The FOE model has demonstrated its applicability in fitting physical devices or systems, such as supercapacitors [24][25][26][27], ferromagnetic core coils [28,29], and on-chip inductors [30], and so on [31,32] producing more satisfactory fitting results than the conventional integer-order model.…”
Section: Introductionmentioning
confidence: 99%